Komunikacja niewerbalna a tłumaczenie symultaniczne: aspekt empiryczny - Rachut, Konrad (Studia Rossica Posnaniensia, 2021)
Bearing in mind the prime principle of audiovisual integration in human communication (Seeber 2012, 2017), the author discusses the empirical aspects of the correlation between nonverbal communication and simultaneous interpreting. Having established that kinesics and prosody indeed can have a positive impact on understanding one’s message, he conducts an experiment in which he compares the quality of the interpretations performed by MA students of English and Russian philology divided into audio and audio-visual groups in the case of English-Polish and Russian-Polish simultaneous interpreting. He focuses specifically on two categories of gestures – illustrators and emblems. Ultimately, he discovers a tangible relation between having the ability to see the speaker and the accuracy of interpreting the speaker’s speech. However, the limitations of the experiment do not allow for making universal conclusions on the basis of its results, as it should become operationalised and replicated.